2012
DOI: 10.1111/j.1439-0426.2012.02040.x
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive biology ofPlagioscion squamosissimus(Heckel, 1840) in the Pará River estuary (Amazon Estuary)

Abstract: Summary This study describes the reproductive biology of the South American silver croaker Plagioscion squamosissimus (Heckel, 1840) in the Pará River estuary. Data were collected bimonthly from June 2007 to May 2008. In all, 334 specimens were examined. The gonads were processed with histological techniques, and the ovaries were subjected to morphometric analysis. The length at first maturity (L50) values were 16.14 and 21.43 cm total length for females and males, respectively. The sex ratio based on the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 21 publications
2
16
1
2
Order By: Relevance
“…Our results contrast with other studies in which these species exhibited greater reproductive intensity during the hottest and rainiest months of the year (Braga, 2001;Carnelós & Benedito-Cecilio, 2002;Luiz, Velludo, Peret, Filho, & Peret, 2011;Barbosa et al, 2012). For C. monoculus the statistical analysis showed that the species did not reproduce throughout the year, but showed a long reproductive period that was not markedly seasonal.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Our results contrast with other studies in which these species exhibited greater reproductive intensity during the hottest and rainiest months of the year (Braga, 2001;Carnelós & Benedito-Cecilio, 2002;Luiz, Velludo, Peret, Filho, & Peret, 2011;Barbosa et al, 2012). For C. monoculus the statistical analysis showed that the species did not reproduce throughout the year, but showed a long reproductive period that was not markedly seasonal.…”
Section: Discussioncontrasting
confidence: 56%
“…Souza et al (2008) considered the size at first maturation to be the shortest length at which individuals at the advanced maturation stage were found. However, the logistic regression method used in our study and by Rocha et al (2006), Camargo andJúnior (2007), Santos, Gonzalez and Araújo (2001), and Barbosa, Rocha and Frédou (2012) is more robust and more suitable for this analysis (King, 2007), therefore, the estimates made using this method are more reliable. According with King (2007) other factors that may have caused the difference in size at first maturation include: (1) Food availability: In the Santa Cruz Reservoir P. squamosissimus and C. monoculus had an abundance of food, as suggested the length-weight relationship with a b value near 3, so the fish could allocate enough energy to growth and early maturation; (2) Absence of predators: With less energy expended to avoid predators, more energy could be allocated to maturation; and (3) High and constant temperature throughout the year in the region: at high temperature, the growth rate is higher.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The P 50 values were compared with those for first sexual maturity (L 50 ) available in Vásquez et al (2009) for B. vaillantii, Fabré et al (2000) for Brachyplatystoma rousseauxii, and Barbosa et al (2012) for Plagioscion squamosissimus.…”
Section: Body Length and Catch Probabilitymentioning
confidence: 99%
“…The L50values for B. vaillantii,B. rousseauxii and P. squamosissimus were obtained from Vásquez et al (2009), Fabré et al (2000 and Barbosa et al (2012), respectively. …”
Section: Body Length and Catch Probabilitymentioning
confidence: 99%